Mycorrhizal colonization and diversity and corn genotype yield in soils of the Cerrado region, Brazil - Aquino, Sueli Da Silva [UNESP]; Scabora, Márcia Helena [UNESP]; Andrade, João Antonio Da Costa [UNESP]; Da Costa, Sandra Maria Gomes; Maltoni, Kátia Luciene [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP] (Universidade Estadual de Londrina, 2015)
The degree of interaction between arbuscular mycorrhizal fungi (AMF) and host plants appears to depend on plant genotype, which differentially promotes symbiosis and leads to different degree of mycotrophism. The aim of the present study was to assess root colonization, spore density, and diversity of AMF, as well as yield of corn (Zea mays) genotypes in soil from the Cerrado region of Brazil. Number of spores (NS), mycorrhizal colonization (COL), plant and ear height, dry weight (DW), and grain yield (GY) were assessed in inbred lines and their hybrids. Randomized blocks were used for the experimental design, with 30 treatments (genotypes) and three repetitions. The experiment was conducted on the farm of the UNESP-São Paulo State University, Campus of Ilha Solteira, and the plots were composed of two 2-m-long rows, with 0.85 m between rows, and 0.20 m between plants. Qualitative and quantitative changes were observed in fungal compositions, as well as preferential associations between symbiotic partners. Analysis of AMF diversity revealed the presence of 12 species, with Scutellospora calospora and Entrophospora colombiana being the most abundant in all treatments. The species Acaulospora longula, Glomus etunicatum, Glomus macrocarpum, and Gigaspora margarita exhibited preferential associations with certain genotypes. COL and GY differed among inbred lines and single-cross hybrids and the significant correlations between COL and the DW and GY showed positive interactions between the plants and AMF. There was no correlation between heterosis for GY and heterosis for colonization. These single-cross hybrids HS83 × E3 and D3 × F5 exhibited high GY, evidencing a productivity potential for the low technological condition used.
Keywords: Arbuscular mycorrhizal fungi; Inbred lines; Single-cross hybrids; Species richness; Zea mays